Building a Cultural Heritage Preservation System in Poland - Purchla, Jacek (Journal of Public Governance, 2011)
After its political transformation, Poland had to face new challenges and threats concerning its cultural heritage. The Congress of Polish Culture, organised in Cracow in September 2009, prepared a comprehensive report on the cultural heritage preservation system in Poland after 1989. The authors of the report indicate three phenomena that can have a significant impact on the future of Polish historical monuments: an accelerating process of transformation of building stock, leading to stronger pressures of economic factors on the cultural landscape; a growing demand forheritage as a backlash against the homogenising effects of globalisation and a result of the increasingly important economic role of tourism; a shift in focus from the value of heritage to the needs of society. Th is new approach to heritage can be described as a change in its ontological status.The existing legal and financial tools of monument protection were adapted to a static situation typical of a centrallyplanned economy and a command-and-quota system. Today, we need to create a new effective programme of heritage management that would satisfy local communities who, together with the owners and users of monuments, are crucial for heritage protection.